2012
DOI: 10.1016/j.jorganchem.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Square-planar metal(II) complexes containing ester functionalised bis(phosphino)amines: Mild P−N methanolysis and Carene−H cyclometallation

Abstract: a b s t r a c tThe synthesis of three new ester functionalised bis(phosphino)amines Ph 2 PN{R}PPh 2 [R ¼ C 6 H 4 (3-CO 2 Me) 1a; C 6 H 3 (3,5-CO 2 Me) 2 1b; C 6 H 4 (4-CO 2 Me) 1c] upon stoichiometric reaction of Ph 2 PCl and the appropriate H 2 N{R} in Et 2 O is described. Reaction of 1 equiv. of 1aÀc with MCl 2 (cod) (M ¼ Pt, Pd) in CH 2 Cl 2 afforded the dichlorometal(II) complexes PtCl 2 (1a) 2a, PtCl 2 (1b) 2b, PtCl 2 (1c) 2c and PdCl 2 (1b) 2`b respectively. The corresponding dibromo (and diiodo) platinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Smith and colleagues reported the synthesis of two other DPPA-type ligands of general formula Ph 2 PN­(R)­PPh 2 [R = C 6 H 4 (3-CO 2 Me) ( 102 ), C 6 H 4 (4-CO 2 Me) ( 103 )] (Scheme ), which carry on their nitrogen atom a mono-ester-aryl function . These diphosphine ligands exhibit a single 31 P NMR resonance at 69.0 ( 102 ) and 68.5 ( 103 ) ppm, very close to that of the bis-ester derivative 99 (see above and Table ).…”
Section: Oxygen-based Functionalizationsmentioning
confidence: 66%
See 2 more Smart Citations
“…Smith and colleagues reported the synthesis of two other DPPA-type ligands of general formula Ph 2 PN­(R)­PPh 2 [R = C 6 H 4 (3-CO 2 Me) ( 102 ), C 6 H 4 (4-CO 2 Me) ( 103 )] (Scheme ), which carry on their nitrogen atom a mono-ester-aryl function . These diphosphine ligands exhibit a single 31 P NMR resonance at 69.0 ( 102 ) and 68.5 ( 103 ) ppm, very close to that of the bis-ester derivative 99 (see above and Table ).…”
Section: Oxygen-based Functionalizationsmentioning
confidence: 66%
“…Both dinuclear Au(I) complexes were characterized in the solid-state by XRD studies and revealed a typical linear coordination geometry for the Au(I) 22), which carry on their nitrogen atom a mono-ester-aryl function. 72 These diphosphine ligands exhibit a single 31 P NMR resonance at 69.0 (102) and 68.5 (103) ppm, very close to that of the bis-ester derivative 99 (see above and Table 9). 71 The authors investigated the coordination chemistry of ligands 102 and 103, along with that of ligand 99, toward the group 10 metal centers of [MX 2 (COD)] (M = Pt, Pd; X = Cl, Br, I) (Scheme 22).…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu contacts [40]. We showed that PNP ligands, with ester groups on the central -N(arene)-core (e.g., 2g) could be synthesised from the amine/ClPPh 2 /NEt 3 in Et 2 O [41]. Ligands such as 2h could be prepared from Me 3 SiN(R')SiMe 3 /2 equiv.…”
Section: Synthesis Of Selected Examplesmentioning
confidence: 99%
“…[25] The main bond lengths and angles of the later, along with those of complexes 1 and 2 [17], are listed in Table 2. It should be noted that the structure of one [Pd(P,P)I 2 ] complex (bearing one Me and three Ph as R groups and R′ = i Pr) [26] and two [Pt(P,P)I 2 ] complexes (R = Ph, R′ = C 6 H 4 (CO 2 CH 3 ) [27] or Ph [28]), have been reported and are available in the CSD.…”
Section: Structural Features Of Complexmentioning
confidence: 99%